2014
DOI: 10.4088/jcp.13r08800
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Antidepressant Treatment of Interferon-Induced Depression in Chronic Hepatitis C

Abstract: Administration of SSRIs before starting antiviral treatment reduces the incidence of interferon-induced depression, with a relatively moderate prophylactic impact and good tolerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 0 publications
1
26
0
1
Order By: Relevance
“…37 Patients treated with the inflammatory cytokine, IFN-α, developed clinically significant depression. 13,14 Similarly, patients with rheumatoid arthritis, psoriasis, and cancer, treated with anti-TNF, showed improvement in their depression symptoms. [38][39][40] Patients responded to anti-TNF with improvement in the severity of depression with treatment-resistant depression along with high levels of inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Patients treated with the inflammatory cytokine, IFN-α, developed clinically significant depression. 13,14 Similarly, patients with rheumatoid arthritis, psoriasis, and cancer, treated with anti-TNF, showed improvement in their depression symptoms. [38][39][40] Patients responded to anti-TNF with improvement in the severity of depression with treatment-resistant depression along with high levels of inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that up to 50% of patients treated with interferon-α developed clinically significant depression. 13,14 This inflammatory model of depression provides a putative link between infection and depression. The association between typhoid fever and neuropsychiatric illness is documented in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Udina et al 8 found that the NNT was 12 (95% CI, 7-38) for the efficacy of selective serotonin reuptake inhibitors in the prevention of occurrence of a major depressive episode during antiviral treatment of chronic hepatitis C infection. The interpretation of 95% CIs was discussed in an earlier article in this column.…”
Section: Calculating the Nntmentioning
confidence: 99%
“…Moreover, meta-analyses show increased inflammatory parameters in the blood of patients with MDD [4, 5]. Alternatively, patients undergoing cytokine therapy develop depressive symptoms [6, 7] and experimental-induced inflammation promotes mood deterioration in healthy subjects [8]. Furthermore, elevated inflammatory markers predict a poorer response to antidepressants (AD) while non-responding patients to AD show persistently elevated inflammation [9].…”
Section: Introductionmentioning
confidence: 99%